Disentangling objective characteristics of learning situations from subjective perceptions thereof, using an experience sampling method design - Moeller, Julia; Viljaranta, Jaana; Kracke, Bärbel; Dietrich, Julia (Frontline Learning Research, 2020)
This article proposes a study design developed to disentangle the objective characteristics of a learning situation from individuals’ subjective perceptions of that situation. The term ‘objective characteristics’ refers to the agreement across students, whereas ‘subjective perceptions’ refers to inter-individual heterogeneity. We describe a novel strategy for assessing and disentangling objective situation characteristics and subjective perceptions thereof, propose methods for analyzing the resulting data, and illustrate the procedure with an example of a first study using this design to examine situational interest in 155 university students. Situational interest was assessed nine times per weekly lecture with three measurement time points per person and a rotated multi-group schedule. Assessments took place over the course of an entire semester of ten weeks. One of the advantages of the proposed design is that ‘objective’ group agreements can be disentangled from subjective deviations from the group’s average at each of the nine measurement time points per weekly lecture. Furthermore, the proposed design makes it possible to study the development of both subjective and objective parameters across the time span of one weekly lecture and an entire semester, while the burden for each person is kept relatively low with three beeps per lecture.